Business for peace: How entrepreneuring contributes to Sustainable Development Goal 16 - Peter Jack Gallo; Santiago Sosa; Andres Velez-Calle (BRQ Business Research Quarterly, 2023)
We examine entrepreneurial ventures in a post-conflict context to identify practices that are helpful for companies operating in conflict zones while contributing to the United Nations' Sustainable Development Goal 16 (SDG 16)-Peace, Justice, and Strong Institutions. Using emancipatory entrepreneuring as our theoretical lens, we analyze entrepreneurial ventures where ex-combatants seek to create economic opportunities and challenge the status quo of violence, poverty, and inequality in their rural communities. We develop four qualitative case studies of ex-combatant entrepreneurship to identify the activities that enable them to grow their businesses while promoting peace. We identify actor distance and entrepreneurial stage as key dimensions for defining a matrix of relationship arrangements that facilitate venture success and peacebuilding efforts. We conclude with a summary of our contributions and implications for research and practice.
Keywords: D63; D74; H56; L14; L26; 650; Business for peace; emancipatory entrepreneuring; entrepreneurship; extreme context; SDG 16